Solanum nigrum Ethanolic Extract (SNE) Increases Cytotoxic Activity of Doxorubicin on MCF-7 Cell - Putri, Dyaningtyas Dewi Pamungkas; Rivanti, Erlina; Istiaji, Raditya Prima; Meiyanto, Edy (Indonesian Society for Cancer Chemoprevention, 2021)
Leunca (Solanum nigrum L.) is a potential source of natural anticancer agents. Solanum nigrum L. ethanolic extract (SNE) has cytotoxic activity in several cancer cell lines. We aimed to evaluate the ability of SNE to increase MCF-7 cell sensitivity to doxorubicin as a chemotherapeutic agent for breast cancer. Cell viability of SNE and its combination treatment with doxorubicin were conducted by 3-(4,5-dimethylthiazol-2-yl)-2.5-diphenyltetrazolium bromide (MTT) assay, and apoptosis assay was analyzed by Ethidium bromide-acridine orange method. The SNE showed a cytotoxic effect in the MCF-7 cell line with IC50 50 μg/mL. Combination treated DOX-SNE resulted in a combination index (CI) value of 0.21, indicating strong synergism SNE and doxorubicin. The SNE 25 μg/mL combined with doxorubicin 100 nM optimally induced apoptosis of MCF-7 cells. We concluded that SNE is the potential to be developed as a co-chemotherapeutic agent through apoptosis induction though the molecular mechanism need to explore.Keywords: Solanum nigrum L. herb ethanolic extract, doxorubicin, MCF-7, apoptosis.